Krisis Ilmu Pengetahuan Modern: Menuju Metodologi Partisipatif - Hilwati Hindersah (The Institute for Research and Community Services, Institut Teknologi Bandung, 2005)
Positivistic methodology has a very determining role in the development of modern science. To begin with, science is applied only to the physical universe. Science began to focus on this physical world and quickly flourished into a philosophical position that was quickly embraced as the reigning worldview for the modern age. This view further advocated an empirical skepticism in which nothing about the universe